1997
DOI: 10.1029/96jd03126
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric water vapor estimate by a differential absorption technique with the polarisation and directionality of the Earth reflectances (POLDER) instrument

Abstract: Abstract. The polarization and directionality of the Earth reflectances (POLDER) instrument, to be launched in 1996 on the Japanese ADEOS (advanced Earth observing satellite) platform includes a channel which covers the 910 nm water vapor absorption band (near IR), as well as a channel centered at 865 nm. An estimate of the total atmospheric water vapor content can be derived from the ratio of the two reflectance measurements. In addition to the spectroscopic parameterization, the major uncertainties of this e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…This technique is based on the differential absorption method, which assumes that the transmittance of one water vapour absorption channel can be estimated using the ratio of the measured radiances in the absorption channel and at least one window channel. The technique is described in Gao and Goetz (1990) ;Frouin, Deschamps, and Lecomte (1990); Kaufman and Gao (1992); Gao et al (1992;, Carrère and Conel (1993); Borel, Clodius, and Johnson (1996); Bouffies et al (1997); Schläpfer et al (1998); Thai and Schonermark (1998); Vesperini, Bréon, and Tanré (1999); Bennartz and Fischer (2001); Gao and Kaufman (2003) and Sobrino, El Kharraz, and Li (2003). For the MODIS sensor, the NIR water vapour absorption channels are 17, 18, and 19 (centred at 0.905, 0.936, and 0.940 µm, respectively; see Table 1), and the NIR transparent channels usually chosen (in the three water vapour absorption channels) are 2 and/or 5 (centred at 0.865 and 1.24 µm, respectively; see Table 1).…”
Section: Global Modis Nir Water Vapour Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique is based on the differential absorption method, which assumes that the transmittance of one water vapour absorption channel can be estimated using the ratio of the measured radiances in the absorption channel and at least one window channel. The technique is described in Gao and Goetz (1990) ;Frouin, Deschamps, and Lecomte (1990); Kaufman and Gao (1992); Gao et al (1992;, Carrère and Conel (1993); Borel, Clodius, and Johnson (1996); Bouffies et al (1997); Schläpfer et al (1998); Thai and Schonermark (1998); Vesperini, Bréon, and Tanré (1999); Bennartz and Fischer (2001); Gao and Kaufman (2003) and Sobrino, El Kharraz, and Li (2003). For the MODIS sensor, the NIR water vapour absorption channels are 17, 18, and 19 (centred at 0.905, 0.936, and 0.940 µm, respectively; see Table 1), and the NIR transparent channels usually chosen (in the three water vapour absorption channels) are 2 and/or 5 (centred at 0.865 and 1.24 µm, respectively; see Table 1).…”
Section: Global Modis Nir Water Vapour Algorithmsmentioning
confidence: 99%
“…Many of these methods rely on backscattered solar radiation near the 1 µm band (e.g. Conel et al 1988;Frouin, Deschamps, and Lecomte 1990;Gao and Goetz 1990;Kaufman and Gao 1992;Carrère and Conel 1993;Borel, Clodius, and Johnson 1996;Bouffies et al 1997;Schläpfer et al 1998;Thai and Schonermark 1998;Vesperini, Bréon, and Tanré 1999;Gao and Kaufman 2003;Sobrino, El Kharraz, and Li 2003;Albert et al 2005). We are specifically interested in water vapour measurements from the Moderate Resolution Imaging Spectroradiometer (MODIS) because, in 2007, the University of Oviedo in Asturias (Spain) acquired an antenna enabling us to obtain MODIS data in real time.…”
mentioning
confidence: 99%
“…Near-infrared measurements in water vapor absorbing bands can be used to determine total column water vapor amount over bright surfaces [1]. Figure 1a illustrates the relation between 910 nm / 865 nm reflectance ratio (R) measured by POLDER over bright ocean (sunglint) and the product of air mass factor (m) by UH2O measured by AMSR-E. Vesperini et al [2] proposed a polynomial function to fit the observed relation and obtain a simple parameterization.…”
Section: Retrieval Of Total Column Water Vapor Content From Near-infrmentioning
confidence: 99%
“…The ratio of top of atmosphere reflectances in two close near infrared bands (one absorbing and one window channel) can be used to retrieve water vapor amount [1]. For POLDER, Vesperini et al [2] proposed a polynomial function to parameterize the non linear relation between the air mass weighted total column water vapor amount and the reflectances ratio.…”
Section: Introductionmentioning
confidence: 99%
“…The differential absorption technique utilizing this region of spectrum assumes, in general, that the integrated water vapour content is related to the transmission in a spectral channel affected by the water vapour absorption and that the transmission can be estimated using the radiance ratio of two bands -absorption and non-absorption ones. It comes from the simplification of the Lambert's law (Gao & Goetz, 1990;Bouffiès et al, 1997;Tahl & von Schoenermark, 1998). As the assumptions undergoing the theory cannot be true in reality, nonlinear relationships are used in practice.…”
Section: Water Vapourmentioning
confidence: 99%